PELATIHAN KUESIONER PRA SKRINING PERKEMBANGAN (KPSP) TERHADAP PENGETAHUAN GURU PAUD: Literature Review - Diana (2020)
The growth and development of children is very important to be monitored, but conversely many parents who are interested do not pay attention to the happy growth and development. This is a large part that underestimates the growth, and they think about the development that does not need to be reviewed, later also at their age will be able to by itself. Meanwhile, not all things are like that, and for this reason training on PDQ knowledge is needed, which is needed by PAUD teachers, community services, and development so that they are more sensitive to growth and development. The purpose of this literature review is to make a literature analysis related to the Pre Development Screening Questionnaire (PDQ) training on the knowledge of PAUD teachers. This Literature Review was taken from a database (Scopus, PubMed, Goggle Scholar, Ebsco) using Indonesian and English in the last 5 years. Searching the research literature used keywords such as "child development", "early childhood education teacher" and "pre-screening development questionnaire". The initial studio search results from all databases used were obtained as many as 165 article and two formulas were distributed based on PICO and CRAAP methods. A total of 4 article were selected for analysis. Factors of teacher knowledge and caregivers of children, age, last education, length of work, work, understanding, length of interaction and number of children can cause developmental disorders in children. The teacher's knowledge and parenting to improve child development by screening as early as possible can reduce the number of children who correct deviations in development.